REFLECTION AS A DETERMINANT OF SELF-FORMATION: ANALYSIS AND RESEARCH PERSPECTIVES (Psychology Travelogs, 2023)
In the conditions of constant and rapid changes in contemporary society, the issue of self-formation gains particular significance and its impact on identity formation. However, to deeply understand this process, it is important to turn to the understanding of reflection as a determinant of self-formation.Reflection, in turn, is characterized as an active and internal process involving contemplation and understanding of one's experiences, beliefs, and values. This internal dialogue emerges as a crucial factor in shaping the distinctive self-definition of each individual.Self-formation, a continuous and dynamic process encompassing the definition of personal goals, values, and life path, is a focal point. In our investigation, the goal is a comprehensive examination of the interplay between reflection and self-formation. We seek to elucidate the reciprocal influence between the two and uncover potential pathways for optimizing this intricate process. As we delve into this exploration, our aspiration is also to identify key facets that warrant additional scientific investigation, aiming for a more profound and nuanced understanding of this complex relationship.The objective of this article is to conduct a thorough exploration of the role of reflection as a determinant in the self-formation of personality, aiming to identify and analyze the fundamental factors influencing the interaction between reflection and the shaping of one's identity. Furthermore, our goal is to delve into the impact of this intricate process on the ongoing formation and development of an individual's personality. In addition to this, we will endeavor to delineate key aspects that warrant further scholarly investigation, seeking a more nuanced and complete understanding of the complex interplay between reflection and self-formation.
Keywords: Reflection; self-formation; developmental psychology; self-awareness; self-development